2008
DOI: 10.1002/pbc.21663
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial iron overload in transfusion‐dependent pediatric patients with acute leukemia

Abstract: For patients who regularly receive blood transfusions, cardiac failure is the major cause of death. This is most alarming because it progresses rapidly and is difficult to manage. We present three pediatric patients with acute leukemia whose therapy-induced anemia was treated with different amounts of red blood cell concentrates (RCC). In all patients, a liver iron overload was measured by super-conducting interference device (SQUID) biosusceptometry and magnetic resonance imaging (MRI). MRI is a rapid, noninv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
1
14
0
1
Order By: Relevance
“…Although the absence of measurable cardiac iron is a pertinent negative finding that seems reassuring, caution is warranted as isolated case reports of cardiac iron loading have been published (10,28) and the problem may have been under-represented in our cohort. Furthermore, much remains unknown about the fate of transfusion-derived iron during pediatric cancer treatment.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Although the absence of measurable cardiac iron is a pertinent negative finding that seems reassuring, caution is warranted as isolated case reports of cardiac iron loading have been published (10,28) and the problem may have been under-represented in our cohort. Furthermore, much remains unknown about the fate of transfusion-derived iron during pediatric cancer treatment.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, much remains unknown about the fate of transfusion-derived iron during pediatric cancer treatment. Research is needed to elucidate how normal iron homeostasis might be modified in this population through suppression of erythropoiesis by chemotherapy, the inflammatory effects of infections and tissue breakdown, altered nutrition, and circulating factors emanating from the neoplasms themselves that could affect organ function (10,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, those patients were exposed to blood transfusions over 5 to 6 years and subsequently underwent regular phlebotomy because their iron overload was diagnosed after the completion of chemotherapy. 16 Although the cardiac iron levels in their patients and ours are not usually associated with cardiac dysfunction, they do indicate substantial exposure to toxic free iron. The identification of accelerated iron overload should prompt evaluation for underlying etiology.…”
Section: Discussionmentioning
confidence: 57%
“…Our patient's cardiac T2* of 15.6 milliseconds indicated moderate cardiac iron load. 15 Lutz et al 16 reported 2 other children with ALL who developed cardiac iron overload, where the cardiac T2* values were 19 and 20 milliseconds, respectively. However, those patients were exposed to blood transfusions over 5 to 6 years and subsequently underwent regular phlebotomy because their iron overload was diagnosed after the completion of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%